The activation energy for Mg acceptor in AlxGa1-xN alloys in the whole composition range. (September 2017) - Zhao, Chuan-Zhen; Wei, Tong; Chen, Li-Ying; Wang, Sha-Sha; Wang, Jun
Abstract: The activation energy for Mg acceptor in Alx Ga1-x N alloys is investigated. The modified effective mass model is used to describe the activation energy for Mg acceptor in Alx Ga1-x N alloys. It is found that the composition dependence of the activation energy for Mg acceptor in Alx Ga1-x N is very different from that in Inx Ga1-x N. It is mainly due to three factors. In addition, it is found that the energy difference between the Mg acceptor level in Alx Ga1-x N and the VBM of GaN is very small in a very large composition range, which is very helpful for us to use the Mg-doped AlGaN/GaN superlattice structures to increase the free-hole concentration. Graphical abstract: Highlights: The modified effective mass model is used to describe the activation energy for Mg acceptor in Alx Ga1-x N alloys. The factors which influence the activation energy for Mg acceptor are analyzed. The Mg acceptor level in Alx Ga1-x N is very close to the VBM of GaN in a very large composition range.